Antioxidant, antibacterial, in vitro, and in silico α-glucosidase inhibition activities and chemical profiling of Usnea cornuta Korb - Deepa Karki; Anuraj Phunyal; Tika Ram Lamichhane; Deepika Karki; Achyut Adhikari (PLoS ONE, 2026)
The total phenolic content and flavonoid content of the Usnea cornuta extract were evaluated as 210.31 ± 2.87 mg GAE/g and 22.42 ± 0.78 mg QE/g, respectively. The crude extract exhibited strong antioxidant activity (IC 50 : 32.91 ± 1.27 µg/mL) and notable anti-diabetic effects via α-glucosidase inhibition, with IC 50 values of 2.59 ± 2.23 µg/mL for the dichloromethane extract. LC-MS analysis identified eleven metabolites like D-mannitol (1), galbinic acid (2), conhypoprotocetraric acid (3), roccellaric acid (4), diffractatic acid (5), haemathamnolic acid isomer (6), conprotocetraric acid (7), constictic acid I (8), salazinic acid II (9), menegazziaic acid (10), and one unknown compound (11). Among these, menegazziaic acid exhibited the strongest binding affinity of −9.7 kcal/mol with the target (PDB ID 3A4A), favorable molecular dynamics, binding free energy (MM/GBSA, and pharmacokinetic profiles. Furthermore, the extract showed strong antimicrobial activity, with inhibition zones of 23 mm and 26 mm at 10 mg/mL against Staphylococcus aureus ATCC 29213 and ATCC 245, respectively. These findings highlight the therapeutic potential of Usnea cornuta , specifically for managing oxidative stress, microbial infections, and type 2 diabetes.